Evaluating the effect of in-situ rainwater harvesting techniques on maize production in moisture stress areas of humbo woreda, wolaita zone, southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2020)
The study was conducted to investigate the effect of different in-situ water harvesting structures as soil moisture conservation techniques under maize crop production in Abela Sippa kebele Wolaita zone, Ethiopia where rainfall variation is affecting agriculture with prolonged dry spells during critical crop growth stages. The experiment was laid out in a Randomized Complete Block Design, with three replications and four treatments. The four treatments used in the study were; Control, Targa, Tie-ridge and Zai pits. Findings from this study revealed that maize grain yield and yield components, such as, grain yield, dry matter biomass, and cob length were highly significant (p